2006
DOI: 10.1155/asp/2006/54868
|View full text |Cite
|
Sign up to set email alerts
|

Vienna MIMO Testbed

Abstract: While the field of MIMO transmission has been explored over the past decade mainly theoretically, relatively few results exist on how these transmissions perform over realistic, imperfect channels. The reason for this is that measurement equipment is expensive, difficult to obtain, and often inflexible when a multitude of transmission parameters are of interest. This paper presents a flexible testbed developed to examine MIMO algorithms and channel models described in literature by transmitting data at 2.45 GH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…Indeed, MATLAB plays a key role in off-line testbeds that are used to prototype state-of-the-art MIMO-OFDM systems [9][10][11][12][13].…”
Section: The Role Of Matlab In the Design And Validation Processmentioning
confidence: 99%
“…Indeed, MATLAB plays a key role in off-line testbeds that are used to prototype state-of-the-art MIMO-OFDM systems [9][10][11][12][13].…”
Section: The Role Of Matlab In the Design And Validation Processmentioning
confidence: 99%
“…Other examples of this type of platforms can be found in (19,20,26,27,28,29,30,31,32,33,34). If the features of the implemented MIMO platform are compared with the others found in the testbeds cited, it can be concluded that:…”
Section: Rf Modulesmentioning
confidence: 99%
“…Rapid prototyping for hardware testbeds (18,19,20)), and the experimental tests they have allowed to perform have been valuable for researchers. In the same way, research in vehicular communications can…”
mentioning
confidence: 99%
“…A full description of the measurement setup can be found in [4]. For our measurements we used the Vienna MIMO Testbed presented in [5,6] and a Matlab implementation of the IEEE 802.16-2004 WiMAX standard [7]. The basic features of the testbed are as follows.…”
Section: Complexity Assessmentmentioning
confidence: 99%